Development of in situ Ophthalmic gel of Dexamethasone Sodium Phosphate and Chloramphenicol: A Viable Alternative to Conventional Eye Drops - Ketan Ranch, Hetal Patel, Laxman Chavda`, Akshay Koli, Furqan Maulvi, Rajesh K. Parikh (Journal of Applied Pharmaceutical Science, 2017)
Context: Poor bioavailability (
Keywords: Full factorial design, response surface methodology, gellan gum, dexamethasone sodium phosphate, chloramphenicol.